Antibacterial Potential of Kaempferia parviflora Rhizome Extract against Staphylococcus aureus ATCC 25923 - Leswara, Dianita Febrina; Larasati, Dwi (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Bacteria are one of the organisms that cause infectious diseases. One of the bacteria that can cause infection is Staphylococcus aureus. Treatment of bacterial infections is by using antibiotics, but using the antibiotics for a long term can cause resistance. It is necessary to look for alternative compounds that can inhibit the growth of Staphylococcus aureus. In the bioprospecting process of medicinal plants, it is not only necessary to rely on empirical information but also to have scientific evidence proven through scientific testing. One of the plants with potential as a medicine is black ginger (Kaempferia parviflora). The aim of this study is to determine the effectiveness of Kaempferia parviflora rhizome in inhibiting the growth of Staphylococcus aureus bacteria. The concentrations of the Kaempferia parviflora extract tested were 25%, 50%, 75%, and 100%. Based on the results, it can be concluded that the ethanol extract of Kaempferia parviflora rhizome has antibacterial activity against the growth of Staphylococcus aureus ATCC 25923 at concentrations of 25%, 50%, 75%, and 100%, with strong antibacterial inhibition. This study is expected to contribute to the field of health in general and pharmacy in particular by developing the potential of Indonesian medicinal plants. The findings of this study will be directed toward the development of formulations with antibacterial activity.